Automatic interconnection rectification for SoC design verification based on the port order fault model. - Chun-Yao Wang (IEEE Transactions on computer-aided design of integrated circuits and systems)
Embedded cores are being increasingly used in large system-on-a-chip (SoC) designs. The high complexity of SoC designs lead the design verification to be a challenge for system integrators. This paper presents an automatic interconnection rectification (AIR) technique based on the port order fault model to detect, diagnose, and correct the misplacements of interconnection that occurred in the integration of a SoC design automatically. The experiments are conducted on combinational and sequential benchmarks. Experimental results show that the AIR can correct the misplaced interconnection exactly within reasonable efforts and, therefore, accelerates the integration verification of SoC designs.